Communist University of London No.8 - Tyler, Chris (University of London Union, 1976)
Cartoon of van driven by ruling-class professors in need of repair jacked up by Marxist literature as police and others investigate. Large red sign in foreground Printed by the Farleigh Press Ltd. (T.U.), Watford, Herts PO-0779